BANJARMASIN CULTURAL CENTER - Aulia Syafitri; Naimatul Aufa (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
Banjarmasin the "City of a Thousand Rivers" boasts rich cultural heritage shaped by its extensive river networks. These rivers not only define the city's geographic characteristics but also play a crucial role in the social, economic, and cultural life of its people. However, modernization has led to the gradual fading of these cultural values. To preserve and promote this invaluable heritage, a cultural development and preservation facility, the Banjarmasin Cultural Center, is proposed. This study aims to design a cultural center that harmonizes local cultural elements with the needs of modern society. The concept of "aruh ganal" (grand celebration) is adopted as the main design approach, where local culture is celebrated and expressed through modern architectural design. An analogy-based approach is used to translate Banjar cultural elements into the design. The result is a cultural center that strengthens Banjarmasin's identity as the "City of a Thousand Rivers" while ensuring the continued relevance of its local cultural heritage in the face of contemporary changes.